2001
DOI: 10.1021/cm010267c
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Nanocrystalline Molybdenum Disilicide (MoSi2) by a Chlorine-Transfer Reaction

Abstract: Reaction of MoCl3 and Si at 500 °C produces phase-pure MoSi2 powders in near-quantitative yields. Use of an inert diluent (LiCl or ZnCl2) enables the production of nanocrystalline powders. The diluent can be subsequently removed by washing with methanol or by sublimation. Consolidation of diluent-free powders by hot pressing at 1400 °C and 375 MPa for 0.5−4 h affords dense compacts (>95% theoretical density) possessing nanocrystalline grains (<50 nm) and exhibiting hardnesses of 15.0−16.3 GPa. This constitutes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 39 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Most CrSi 2 nanowires show the hexagonal cross section which is a common feature for hexagonal compounds. ,, The CrSi 2 nanowires were formed on the Si substrate at 700 °C through the reaction between the in situ generated CrCl 3 and Si atoms from Si substrate, i.e similar to the case to synthesize MoSi 2 crystallite . The CrN nanowires were formed on the quartz wafer at 800 °C through the reaction between CrCl 3 and NH 3 , i.e…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Most CrSi 2 nanowires show the hexagonal cross section which is a common feature for hexagonal compounds. ,, The CrSi 2 nanowires were formed on the Si substrate at 700 °C through the reaction between the in situ generated CrCl 3 and Si atoms from Si substrate, i.e similar to the case to synthesize MoSi 2 crystallite . The CrN nanowires were formed on the quartz wafer at 800 °C through the reaction between CrCl 3 and NH 3 , i.e…”
Section: Resultsmentioning
confidence: 96%
“…similar to the case to synthesize MoSi 2 crystallite. 16 The CrN nanowires were formed on the quartz wafer at 800 °C through the reaction between CrCl 3 and NH 3 , i.e. since the Si element in quartz wafer is inert (only CrN nanoparticles were obtained at 700 °C).…”
Section: Resultsmentioning
confidence: 99%
“…Grain boundaries rather than dislocations in nanocrystalline materials govern the mechanical behavior, resulting in enhancement of mechanical properties. The fracture toughness of nanocrystalline MoSi 2 is as high as 4.8MPa•m 1/2 [15]. Much more property enhancement might be expected of nanocrystalline SiC/MoSi 2 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, works by Gosele et al demonstrated the Kirkendall effect formation of hollow structures resulting from heating interfaces between metal oxide heterostructures at temperatures in the range of 500−800 °C. 2,6 Others have used similar thermally activated solid-state diffusion processes to form unique nanostructures, including Lieber et al, 7 Wang et al, 8 Buhro et al, 9 and others. 10−12 In each case, temperatures over 500 °C were needed to overcome the significant thermal barrier to diffusion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As such, high temperatures (500–2000 °C), high pressures, or combinations of the two are usually necessary, greatly limiting where and how the method can be employed. For example, works by Gösele et al demonstrated the Kirkendall effect formation of hollow structures resulting from heating interfaces between metal oxide heterostructures at temperatures in the range of 500–800 °C. , Others have used similar thermally activated solid-state diffusion processes to form unique nanostructures, including Lieber et al, Wang et al, Buhro et al, and others. In each case, temperatures over 500 °C were needed to overcome the significant thermal barrier to diffusion. In the meantime, conversion of nanostructures has been demonstrated using solution-based (wet) chemistry at significantly lower temperatures, solvent- or solute-mediated ion exchange being an important enabling factor. , For instance, researchers have employed chemical reagents to selectively extract chalcogen anions, or metal cations, , leaving the nanocrystal size and shape intact in the converted product.…”
Section: Introductionmentioning
confidence: 99%